High-risk pregnancy and risk of breastfeeding failure - Eman S. Salama; Mostafa Hussein; Ahmed N. Fetih; Azza M. A. Abul-Fadl; Shimaa A. Elghazally (SpringerOpen, 2024)
Abstract Background There is growing evidence that supports the role of breastfeeding in reducing the burden of non-communicable diseases (NCDs). There are considerable gaps in breastfeeding outcomes in mothers with chronic diseases due to a lack of knowledge and support in the postpartum period. Mothers who have NCDs and pregnancy complications are at risk of breastfeeding failure. Aim To compare breastfeeding outcomes in mothers with NCDs with healthy mothers and determine the underlying challenges that lead to poor outcomes. Methods A prospective cohort study was conducted among 150 women (50 with high-risk pregnancies (HRP) and 100 with normal pregnancies (NP)). They were recruited from those attending the immunization and outpatient clinics at Sohag General Hospital. Mothers were recruited at 34 weeks gestation and were followed up at 2 weeks, 6 weeks, and 6 months after delivery. A pretested and validated questionnaire was used to collect detailed epidemiological, personal, health-related status, medications, hospitalizations, reproductive history, current delivery, and previous breastfeeding experiences. On follow-up they were assessed for breastfeeding practices, their health and health and growth of their children, and social support. Results Delivery by cesarean section and postpartum bleeding were commoner among HRP patients. Initiation of breastfeeding in the 1st hour of delivery was significantly lower among women with HRP than those with normal pregnancies (48.0% versus 71.0%, p = 0.006). The most common reason for not initiating breastfeeding among the NP group was insufficient milk (34.5%), while in the HRP group, it was the mother's illness (80.8%). Skin-to-skin contact with the baby after birth was significantly less practiced in the HRP than in the NP group (38.0% vs 64.0% at p = 0.003). Herbs (such as cumin, caraway, cinnamon, aniseed, and chamomile) were the most common pre-lacteal feeds offered (63.0% in NP vs 42.0% in HRP). Artificial milk was more used in HRP than NP (24.0% vs 4.0%). Breast engorgement was 3 times more common in the HRP compared to the NP group (61.5% vs19.6%). Stopping breastfeeding due to breast problems was 2.5 times higher in the HRP than in the NP group (38.5% vs. 15.2%, p = 0.003). Nipple fissures were twice as common among the NP than among the HRP group ((73.0%) vs. (38.5%), p = 0.026). Exclusive breastfeeding during the period of follow-up was lower in the HRP than in the NP group (40.0% vs 61.0%, p < 0.05) and formula feeding was twice as common in the HRP as in the NP group (34.0% vs. 18.0%, p = 0.015). Child illness was significantly higher among women with HRP than those with NP (66.0% vs 48.0%, p = 0.037). Conclusions Women with HRP are at a high risk of poor breastfeeding outcomes with increased lactation problems and formula feeding rates. Encouraging women especially those with HRP to achieve optimal breastfeeding practices is a simple intervention that can be included in daily practice and may have a positive impact on mothers' health.